Morphology and multigene phylogeny reveal ten novel taxa in Ascomycota from terrestrial palm substrates (Arecaceae) in Thailand - Sirinapa Konta; Saowaluck Tibpromma; SC Karunarathna; Milan C. Samarakoon; L. Suib Steven; Ausana Mapook; Saranyaphat Boonmee; Chanokned Senwanna; A. Balasuriya; Prapassorn D. Eungwanichayapant; KD Hyde (2023)
Arecaceae is one of the important plant families in Thailand, and several of its representative genera are used for food, cosmetics, and energy sources.During the past eight years (2014 to 2022), more than 50 new taxa associated with terrestrial palm substrates have been reported in Thailand.The present study continued the survey of fungi associated with terrestrial palms in Thailand and based on both morphological characteristics and phylogenetic analyses of combined sequence data, fungal taxa belonging to the orders Amphisphaeriales, Diaporthales, Distoseptisporales, Glomerellales, Pleosporales, and Xylariales were identified.A new genus Triseptatospora and nine new species viz., Acremoniisimulans cocois, Acrocalymma arengae, Bartalinia adonidiae, Cytospora calamicola, Distoseptispora licualae, Neopestalotiopsis elaeidis, Pteridiospora arengae, Triseptatospora calami, and Xenoanthostomella calami are described and introduced here.Morphological illustrations, descriptions, and phylogenetic trees which indicate the placement of the new taxa are provided.